Associations of-374T/A Polymorphism of Receptor for Advanced Glycation End Products (RAGE) Gene in Turkish Diabetic and Non-diabetic Patients with Coronary Artery Disease - (:unkn) unknown (INT INST ANTICANCER RESEARCH, 2009)
Background: In this study we aimed to determine the possible risks for the development of coronary artery disease (CAD) in diabetic (DM+) and nondiabetic (DM-) patients according to the -374T/A polymorphism of the receptor for advanced glycation end products (RAGE) gene which affects the function of RAGE itself. Materials and Methods: This study was carried out in 52 non-diabetic and 62 diabetic patients with CAD, and 55 CAD-free, healthy volunteers as controls. The A-T transversion polymorphism at position -374 in the promotor region of the RAGE gene was analyzed by, polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP) techniques. Results: The -374T/A AA genotype-frequency was statistically higher in the whole patient group when compared with the control group (p=0.034), and statistically higher in the DM+ group when compared with the control group (p=0.003). Homozygosity for the -374A allele was found to be higher, but not statistically meaningful, in DM- patients (17.3%) when compared with the control group (13.2%). In this study, in contrast with other studies, we found possesion of the A allele to be an independent risk factor in CAD in patients with diabetes mellitus. Conclusion: Possesion of the -374A allele may contribute to the CAD in diabetic patients with triggering macrophages by increased levels of AGEs.
Keywords: RAGE; coronary artery disease; diabetes mellitus; polymorphism; genetics; VASCULAR-DISEASE; ATHEROSCLEROSIS; DYSFUNCTION; PROMOTER; MELLITUS; RISK